Pengaruh Faktor Sosial-Ekonomi dan Religiusitas Keluarga Muslim terhadap Keputusan Kepemilikan Saham di Indonesia - Shobiyyah Marzuqoh (Journal of Islamic Economics and Finance, 2025)
The participation of Muslim families in Indonesia’s capital market remains relatively low despite increasing access to financial instruments. This low level of stock ownership highlights the need to analyze the influencing factors. This study aims to examine the effect of socio-economic factors and religiosity on stock ownership decisions among Muslim families in Indonesia. The data used are panel data from the Indonesian Family Life Survey (IFLS) for the years 2007 and 2014, consisting of 32,074 observations from 16,037 household heads. The independent variables include gender, age, household size, income, education level, marital status, social expenditures, area of residence, employment status, and religiosity. The analysis was conducted using probit regression, supported by likelihood ratio tests, goodness-of-fit measures, and marginal effects analysis. The results show that most socio-economic and religiosity variables significantly influence stock ownership decisions. These findings indicate that the investment behavior of Muslim families is shaped by a combination of structural characteristics and religious values. The implications of this study may serve as a foundation for developing contextual and inclusive financial literacy policies.